PERBEDAAN ANGKA KUMAN STREPTOCOCCUS ANTARA SANTRIWATI YANG TIDAK PUASA DENGAN YANG PUASA DI PONDOK PESANTREN WAHID HASYIM SLEMAN YOGYAKARTA - Riajeng Tri Jatworo; Siti Sulastri; Sutrisno Sutrisno (Journal of Oral Health Care, 2014)
In Indonesia, infectious disease is a disease that often occurs, either that infectsthe outer limbs and in the oral cavity. In the oral cavity can affect soft tissue andhard tissue. The infection is caused by a bacteria that is actually a normal flora in theoral cavity. People who fasting their, oral cavity is dry because there is no food thatchewed all day, so saliva secreted activity is reduced. This causes the anaerobicsulfur-producing Streptococcus species including multiply in the mouth. Therefore,people fastings, bad breath can not be avoided. More over, if oral hygiene is notmaintained will develop caries, gingivitis and periodontitis. This research aims to provethe absence of difference the number of streptococcus bacteria between fasting andnot fasting. Study of true experimental design laboratory with post-only control groupdesign. The research was conducted in 2012. The location of recearch at WahidHasyim, boarding school, Sleman, Yogyakarta. The subjects of this reserarch were15 female students are not treated been fasting and 15 female students were fastingas a control group. At the beginning of the recearch subjects who were not fasting andfasting were commanded to collect 1 ml saliva into the pot with splinting method.Samples were taken to laboratory to do the calculations process of streptococcusbacteria. Analysis of data using statistical tests Mann – whitney test with a significancy0.004 < 0.01. The calculations of the streptococcus prove the absence ofdifference the number of bacteria between female students who were not fast - theaverage was 2971 × 106 CFU / ml with female students who were fast – the averagewas 4128 × 106 CFU / ml. This study proved that the number of streptococcus bacteriaon the female students who were not fast lower than female students who werefast.